2017
DOI: 10.1038/srep44712
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Coupling Behavior of Stacked Heterostructures Based on MoS2, WS2, and WSe2

Abstract: The interlayer interaction of vertically stacked heterojunctions is very sensitive to the interlayer spacing, which will affect the coupling between the monolayers and allow band structure modulation. Here, with the aid of density functional theory (DFT) calculations, an interesting phenomenon is found that MoS2-WS2, MoS2-WSe2, and WS2-WSe2 heterostructures turn into direct-gap semiconductors from indirect-gap semiconductors with increasing the interlayer space. Moreover, the electronic structure changing proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 50 publications
(63 reference statements)
3
61
0
Order By: Relevance
“…E E E = E e e e x . As the valence band maximum and conduction band minimum at the K point are primarily composed of the d orbitals of the metal atoms 49,50 , electrons and holes will, to a good approximation, reside in the middle of their respective layers. We are therefore able to freeze their out-of-plane motion, which effectively makes solving Eq.…”
Section: Interlayer Excitonsmentioning
confidence: 99%
“…E E E = E e e e x . As the valence band maximum and conduction band minimum at the K point are primarily composed of the d orbitals of the metal atoms 49,50 , electrons and holes will, to a good approximation, reside in the middle of their respective layers. We are therefore able to freeze their out-of-plane motion, which effectively makes solving Eq.…”
Section: Interlayer Excitonsmentioning
confidence: 99%
“…26 The characteristics of van der Waals heterostructures are represented not only by the constituent monolayers but also by the interactions among the layers. Recently, various types of van der Waals heterostructures based on MoS 2 have exhibited several interesting electrical, optical, and magnetic properties, [27][28][29][30][31][32][33][34][35][36][37][38][39] but none has reported the mechanism of interface interactions (vdW heterostructures) between MoS 2 and Si 2 BN. We have chosen a 2D Si 2 BN (ref.…”
Section: Introductionmentioning
confidence: 99%
“…WS 2 /MoS 2 is known to form a so‐called type II heterostructure, as shown in Figure , which can effectively separate electron–hole pairs at the interface . Theoretical calculations showed that the valence band maximum was mainly occupied by the d orbital of W in the WS 2 layer, whereas the conduction band minimum primarily originated from the d orbital of Mo in the MoS 2 layer . As a result, the Fermi level of the WS 2 /MoS 2 heterostructure was shifted and appeared between the CBM of MoS 2 and the VBM of WS 2 .…”
Section: Resultsmentioning
confidence: 99%